Exchange Rate Misalignment and Its Relationship to Output Growth in South Africa - Nguyen, Ha (World Bank, Washington, DC, 2018)
This paper establishes a simple theory-based real exchange rate (RER) Misalignment Index for countries around the world from 1950-2014, and shows that South Africa’s RER has been undervalued over the last decade. For the most recent year of 2014, depending on the proxy for productivity, it is undervalued from about 15 percent to 18 percent. The analysis suggests that terms of trade fluctuations explain a large part of the undervaluation. This study is a background note for the South Africa Systematic Country Diagnostic.